2012
DOI: 10.1128/mcb.06138-11
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk between Immunoglobulin Heavy-Chain Transcription and RNA Surveillance during B Cell Development

Abstract: Immunoglobulin (Ig) genes naturally acquire frequent premature termination codons during the error-prone V(D)J recombination process. Although B cell differentiation is linked to the expression of productive Ig alleles, the transcriptional status of nonfunctionally recombined alleles remains unclear. Here, we tracked transcription and posttranscriptional regulation for both Ig heavy-chain (IgH) alleles in mice carrying a nonfunctional knock-in allele. We show that productively and nonproductively VDJ-rearrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 54 publications
8
39
0
Order By: Relevance
“…RNase-treated cells showed no signals, demonstrating that we were measuring RNA (Supplementary Figure S1). These results supported previously published work in which biallelic expression (19,30,31), active chromatin marks and RNA polymerase II binding (30) were found to be associated with both productive and non-productive IgH alleles in mature B cells.
Figure 1.Biallelic expression and comparable nuclear positioning of the two IgH loci relative to PCH in resting and activated B cells.
…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…RNase-treated cells showed no signals, demonstrating that we were measuring RNA (Supplementary Figure S1). These results supported previously published work in which biallelic expression (19,30,31), active chromatin marks and RNA polymerase II binding (30) were found to be associated with both productive and non-productive IgH alleles in mature B cells.
Figure 1.Biallelic expression and comparable nuclear positioning of the two IgH loci relative to PCH in resting and activated B cells.
…”
Section: Resultssupporting
confidence: 92%
“…In 3D-FISH studies, the IgH locus was found to be peripheral also in non-B cells, whereby in EL-4 T cells both IgH alleles were associated with the nuclear lamina but not with PCH (12,44). The proposed model of mono-allelic recruitment to PCH in mature B cells (15,18) was further challenged by the observation that both productive and nonproductive IgH alleles are transcribed in activated splenic B cells (19,30). …”
Section: Discussionmentioning
confidence: 99%
“…1D). However, because of allelic exclusion, only one of the two alleles of each IgH and Igk gene will be expressed as functional antibody chains in single cells (Vettermann and Schlissel 2010), while the transcripts arising from incompletely or nonfunctionally rearranged alleles will be selectively degraded in the cytoplasm (Tinguely et al 2012). If pairing of different Ig genes in the same transcription factories is functionally linked to optimization of antibody production, then one would predict that functionally rearranged Ig genes would be preferred partners in these structures.…”
Section: Resultsmentioning
confidence: 99%
“…5,6 Third, practically all BLs carry translocations of the MYC oncogene into 1 of the Ig loci, mostly the IgH locus.…”
mentioning
confidence: 99%
“…5,6 Third, practically all BLs carry translocations of the MYC oncogene into 1 of the Ig loci, mostly the IgH locus. 7 These translocations either target 1 of the IgH switch regions or they occur as mistakes of somatic hypermutation and are then found within or close to rearranged Ig V region genes.…”
mentioning
confidence: 99%